Compartilhamento do risco de demanda em concess\~oes rodoviárias: Experiências dos países emergentes e perspectivas para o Brasil - Edison Benedito da Silva Filho; Dianifer Leal Borges; Levy Cunha Bravo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The present study aims to analyze the Brazilian and international experience in introducing mechanisms for sharing demand risks in road infrastructure concession contracts to increase the safety and attractiveness of projects for private investments. The model adopted by Chile is discussed in greater detail from an economic and legal point of view, since this country stands out among emerging countries as the most successful case of innovation in the institutional framework for highway concessions, with emphasis on the adoption of revenue guarantees for the concessionaire against the effects of traffic and exchange rate fluctuations, as well as flexibility in contract terms. The evaluation of the selected cases suggests alternatives for improving the regulatory framework for highway concessions in Brazil.
Keywords: R42; H54; 330; road infrastructure; concessions; risk sharing